THE EFFECTIVENESS OF GOOGLE CLASSROOM TOWARD ENGLISH LEARNING ATTITUDE AT SMP NEGERI 4 LEUWILIANG - Muhammad Khoerul Hadist; Eneng R.A; Haris H; Hilda M; Irma Y; Milka K; Nadiva RM; Nur’aeni; Siti K; Siti H; Lia R (STKIP Muhammadiyah Bogor, 2021)
This research was conducted to find out the students of SMP Negri 4 Lowiliang attitude in online learning toward English learning using Google Classroom during covid 19 pandemic. The research was used qualitative methode approach. The questionnaire used as the instrument of research to the thritithstudnets junior high schools. The research discovered there is no significant positive attitude toward using Google classroom in English teaching during covid-19 pandemic, due to some factors which need some future research.